Shifts in Microbial Community Structure and Activity in the Ultra-Oligotrophic Eastern Mediterranean Sea Driven by the Deposition of Saharan Dust and European Aerosols - Guo, Cui; Xia, Xiaomin; Pitta, Paraskevi; Herut, Barak; Rahav, Eyal; Berman-Frank, Ilana; Giannakourou, Antonia; Tsiola, Anastasia; Tsagaraki, Tatiana M.; Liu, Hongbin (Frontiers in Marine Science, 2016)
The atmospheric deposition of gases and particulates from the Sahara Desert and European landmass is an important source of nutrients for the Mediterranean Sea. In this study, we investigated how such atmospheric input might affect bacterial metabolic activities and community dynamics in the ultra-oligotrophic Eastern Mediterranean Sea. Thus a mesocosm simulation experiment was conducted using “pure” Saharan dust (SD) and mixed aerosols (A, polluted and desert origin). The cell specific bacterial production (BP) was stimulated soon after the addition of SD and A, with a higher degree of stimulation being observed in the activity of Alphaproteobacteria than in Gammaproteobacteria, and this lead to significant increases in community BP. Subsequently, a shift between these two dominating classes was observed (such that the proportion of Gammaproteobacteria increased while that of Alphaproteobacteria decreased), along with significant increases in bacterial abundance and chlorophyll a concentration. After a few days, although the abundance of bacteria was still significantly higher in the SD- or A-treated groups, differences in the active community composition between the treatment and control groups were reduced. The altered activity of the two dominating Proteobacteria classes observed, might reflect their different strategies in responding to external nutrient input: with Alphaproteobacteria being more responsive to the direct dust input, whereas Gammaproteobacteria seemed to benefit more from the increase in phytoplankton biomass. In addition, the input of A had a stronger immediate effect and longer lasting influence on changing the active bacterial community composition than did that of SD. Our findings show that episodic atmospheric deposition events might affect the microbial community with regards to their abundance, activity and composition over a short period of time, and thus regulate the function of the microbial community and carbon cycling in oligotrophic waters.